THE IMPORTANCE OF MULTIDETECTOR COMPUTED TOMOGRAPHY IN ACUTE STROKE DETECTION, MONITORING AND SELECTION OF THERAPY - Obreški, Aleksandra; Papović, Ana; Paskaš, Jovo; Stanković, Ana; Jeremić, Danilo; Davidovic, Kristina (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: A stroke is a sudden, focal nonconvulsive neurological dysfunction which occurs due to vascular damage.Aim: The aim of the study was monitoring all patients who reported to the Emergency Center due to some neurological deficit, within a particular period of time.Materials and methods: For a period of one month, we monitored 123 patients who were admitted to the Department of Emergency Diagnostics with some form of neurological deficit and who underwent a native computed tomography (CT) scan and/or angiographic examination of the endocranium. All examinations were performed with the GE BrightSpeed 16 Slice CT scanner (USA). After initial native CT diagnostics, depending on the finding, the examination was either stopped, or the contrast dye was administered and postcontrast examination was performed or CT angiography was carried out.Results: Most of the patients with vascular neurological deficit were between 50 and 59 years old, while a smaller number of patients was registered in the age group of persons younger than 40 years. Most of the female patients were in the 50 – 59 age group, while most of the male patients were between 40 and 49 years old. Of the 94 patients who developed stroke, 78 (83%) patients had ischemic stroke, while 16 (17%) patients suffered hemorrhagic stroke. There is no statistically significant difference in the occurrence of intracerebral hemorrhage and subarachnoid hemorrhage between the sexes. The localization of ischemic brain infarction was in the vascular territory of the anterior cerebral artery (ACA) – 3.2% of the cases, the middle cerebralartery (MCA) – in 38.9% of the cases, the internal carotid artery (ICA) – in 8.4% of the patients, the basilar artery (BA) – in 13.7% of the cases, the posterior cerebral artery (PCA) – in 7.4% of the patients, the vertebral artery (VA) – 9.5% of the cases, and the supratentorial watershed areas of arterial irrigation – in 11.7% of the patients.Conclusion: Native CT examination is the golden standard for the triage of patients with acute stroke. The advantages of using a CT scan in the assessment of patients with acute stroke are that it is practical, precise, quick and available. CT imaging has prognostic value as well, as it can predict the response to the administered thrombolytic therapy.
Keywords: computed tomography; ischemic stroke; hemorrhagic stroke